Analysis of the methodological path of a social mobilization project for tackling Dengue, Zika, and Chikungunya in Minas Gerais - Lucas Barbi; Paloma Coelho; Zélia Maria Profeta da Luz (Saúde e Sociedade, 2025)
Abstract The article investigates the methodological path of Project “Vamo Junto?: Confronting dengue, Zika, and chikungunya” while implementing a popular committee in Betim, Minas Gerais, Brazil, to tackle Dengue, Zika, and Chikungunya. This community-based participatory research consists of a joint construction knowledge process to intervene in reality. The systematic observation of the committee meetings focused on the changes after the committee publicized the project in the Duque de Caxias neighborhood. The need to redesign the dissemination strategy was of communication planning workshops, where the committee emphasized the centrality of tactics and inventive daily practices as paths of action anchored in socio-spatial representations. The workshops contributed to a deeper and more inclusive diagnosis by incorporating the perspectives and experiences of the committee members. They strengthened the committee’s capacity to plan actions more suited to the territorial needs. In this sense, the methodological redesign resulted in an innovation where communication provided the groundwork for diagnosing the territorial problems and potential by making visible voices and meanings not formally included in developing strategies to tackle Dengue, Zika, and Chikungunya.